Pengaruh Budaya Organisasi, Komitmen Organisasi dan Persepsi Karyawan terhadap Kinerja Karyawan - Citra Nanda Cahyaningrum; Dewi Andriani; Rifdah Abadiyah (Jambura Journal of Educational Management, 2025)
In this study, researchers chose the company PT. Japfa Comfeed Indonesia, TBK Gedangan Unit Sidoarjo as the research object has the aim of knowing Organizational Culture, Organizational Commitment and Employee Perceptions of Employee Performance at PT. Japfa Comfeed Indonesia, TBK Gedangan Unit Sidoarjo. This research utilizes quantitative research methods, with the type of data used being primary data (survey). The sampling technique used by researchers was distributing questionnaires to a population of 170 employees with data collected directly from respondents. The data collection technique in this research utilizes a Likert scale. The Likert scale is a tool used to measure attitudes, opinions and perceptions of individuals and groups of people about social phenomena. The data testing analysis technique utilizes Smart Partial Square (SPSS) software version 25. With classic assumption tests of validity and reliability, Outher Model and Inner Model. The research results show that Organizational Culture influences Employee Performance, Organizational Commitment influences Employee Performance, and Employee Perception influences Employee Performance at PT. Japfa Comfeed Indonesia, TBK Gedangan Unit Sidoarjo